DI-079 Brentuximab Vedotin: from Named Patient Program (NPP) to Italian Law 648/96. (24th February 2014) - Rebagliati, G; Bonfichi, M; Zecca, M; Bocchio, F; Gotti, M; Calafiore, L; Cusato, M; Tizzoni, M; Calvi, M
Abstract : Background: Brentuximab vedotin (BV) is an antibody-drug conjugate directed to the protein CD30, which is expressed in classical Hodgkin's lymphoma (HL) and systemic anaplastic large cell lymphoma (sALCL). The drug received conditional marketing authorisation from the European Medicines Agency (EMA) in October 2012 as an orphan drug for relapsed or refractory HL CD30 + and relapsed or refractory sALCL. Since 01/11/2012, BV has been reimbursable by the Italian National Health System (NHS) under Law 648/96 for these indications with specific Italian Medicines Agency (AIFA) monitoring, initially through an Excel tool and, since 15/02/2013, with the new AIFA Registry. Purpose: To evaluate the efficacy and safety of BV in patients with relapsed or refractory HL CD30 + treated in our clinical centre. Materials and methods: A total of 12 patients have been enrolled; treatment has been carried out both under the Named Patient Programme (NPP) and with BV as part of a clinical programme reimbursed by the NHS. The drug was prepared at the Centralised Chemotherapy Preparation Unit of our Hospital Pharmacy. Results: Four patients (3 F-1 M), from the Haematology Unit (3) and Paediatric Oncohaematology Unit (1) of the Foundation IRCCS San Matteo Hospital, from September 2011 to October 2012 were treated in the NPP. Characteristics were (min-max): body weight 44–91 kg, age at starting treatment with BV 13–40 years; number of cycles 6–12; previous treatments: chemotherapy, autologous transplantation (+allogeneic in one case). The responses observed after treatment with BV were: 2 complete remissions (CR), 1 stable disease (SD) and 1 disease progression (DP). There were no suspected adverse drug reactions (ADRs) during treatment with BV. Eight patients (3F and 5M) from the Haematology Unit (7) and the Paediatric Oncohaematology unit (1), received treatment under the NHS from August 2012 to October 2013. Characteristics were (min-max): body weight 51–70 kg, age at starting treatment 18–39 years; previous treatments: several lines of chemotherapy (ABVD, IGEV, bendamustine, etc.), autologous transplantation. Of these, 2 patients are still 'ongoing' (instrumental revaluation not yet performed); 1 patient, after the 4th cycle (partial remission) has continued the treatment at another centre and 2 patients died; we had 1 partial remission and 2 DP in other cases. Two episodes of pulmonary toxicity and one case of severe infusion reaction with bronchospasm were notified as suspected ADRs with BV, but all with outcome improvement. Conclusions: BV is the first monoclonal antibody available for HL treatment; we observed a homogeneous group of patients treated with classic chemotherapy, already receiving a bone marrow transplantation, in which overall survivals obtained with conventional therapies were greatly reduced. Clinical responses noted were substantially comparable to what is described in the literature, with complete responses in 2 patients, not achievable with the other treatment scheme. Based on the results obtained, clinical studies with BV in the front line are pending. No conflict of interest.